1994
DOI: 10.1029/94gl00396
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave splitting in the records of the German Regional Seismic Network

Abstract: Estimates of the parameters of shear‐wave splitting in the records of SKS and SKKS of the new German Regional Seismograph Network (GRSN) for one‐layer model show large azimuthal variations at some stations of the network. It is found that the variations are compatible with the presence of two anisotropic mantle layers in the region of the South German Triangle (SGT); the fast direction in the upper layer is between N‐S and NE‐SW, close to the previously reported estimates of the fast direction in the sub crust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 9 publications
11
42
0
2
Order By: Relevance
“…We also tested the stability of the solutions by exploring all solutions, for which the residual sum remains below a selected percentage of the minimum R min found from (1); here we took 20% level. The main advantage of the new 3-D anisotropic models is that they provide synthetic P-residual spheres which are similar to the observed ones PLOMEROVÁ et al, 1996PLOMEROVÁ et al, , 1997, which is not the case if anisotropic oneor two-layer models with horizontal symmetry axes are used (e.g., MAKEYEVA et al, 1990;SAVAGE and SILVER, 1993;OZALAYBEY and SAVAGE, 1994;BORMANN et al, 1993;VINNIK et al, 1994;SILVER, 1996).…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…We also tested the stability of the solutions by exploring all solutions, for which the residual sum remains below a selected percentage of the minimum R min found from (1); here we took 20% level. The main advantage of the new 3-D anisotropic models is that they provide synthetic P-residual spheres which are similar to the observed ones PLOMEROVÁ et al, 1996PLOMEROVÁ et al, , 1997, which is not the case if anisotropic oneor two-layer models with horizontal symmetry axes are used (e.g., MAKEYEVA et al, 1990;SAVAGE and SILVER, 1993;OZALAYBEY and SAVAGE, 1994;BORMANN et al, 1993;VINNIK et al, 1994;SILVER, 1996).…”
Section: Methodsmentioning
confidence: 94%
“…To explain variations of the fast S polarization azimuth and split time of the SKS waves with backazimuth, VINNIK et al (1994) proposed a two-layer anisotropic model beneath several stations of the German Regional Seismic Network, including the GRF-array, namely beneath the GRA1 station. Two anisotropic layers are described by thicknesses and the fast directions of 83 km and 35°for the upper layer and 300 km and 105°for the lower one.…”
Section: Analysis and In6ersion Of Published Models And Shear-wa6e Spmentioning
confidence: 99%
See 1 more Smart Citation
“…Along the Alpine chain, mountain belt-parallel anisotropy has been already observed (Vinnik et al, 1994;Smith and Ekström, 1999;Barruol et al, 2011;Bokelmann et al, 2013, Bianchi and. However, the average fast axis of SKS splitting showed ~10° (counterclockwise) deviation from the Alps trend in the eastern Alps, along the TRANSALP (Kummerow and Kind, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…This metamorphic event is dated around 23 to 29 Ma (for summary, see Scharf et al, 2013). A deformation acting over 20-30 Ma is indeed enough to create the observed anisotropy assuming typical strain rates (Vinnik et al, 1994;Savage, 1999 Schmid et al, 2004) is suggested to be the main consequence of nearly northward movement of the South Alpine block, acting as a rigid indenter (Ratschbacher et al, 1991;Rosenberg et al, 2004). Experimental results focusing on the indentation effect in the Eastern Alps (Rosenberg et al, 2004(Rosenberg et al, , 2007 have suggested that the oblique indentation N20°E shows the most similarity to the deformation pattern in this region.…”
Section: Resultsmentioning
confidence: 99%